ERROR ON SENTENCE STRUCTURE IN WRITING RECOUNT TEXT AT ELEVENTH GRADE OF SMK NEGERI 2 SIDUAORI - Ndruru, Felistina (Research on English Language Education, 2023)
This research aimed at analyzing the errors on sentence structure in writing recount text made by eleventh grade of SMK Negeri2 Siduaori.This research was designed by using qualitative descriptive method. In analyzing the data, the research used theory of Miles Huberman and Saldana (20:31-33). data reduction, data display, and conclusion drawing verification. The data of this study was taken from the eleventh grade students of SMK Negeri 2 Siduaori. The data of this study are students errors in use past tense.To examine the credibility of this study the researcher used triangulation. The results of this study showed that students made errors because of they are not mastering the pattern of past tense, not mastering tenses,lessmotivation,less vocabulary. It is suggested to the teacher to pay much attention to the error in order to use appropriate strategy in teaching recount text errors, especially in use of the simple past tense, passive and active verbal sentence and in nominal sentence and students can come understand how to write a good recount text.